203 Understanding Cell Migration After Direct Transplantation Into the Spinal Cord: A Tool to Determine the Optimal Transplantation Volume. (August 2015) - Gutierrez, Juanmarco; Moreton, Cheryl L.; Lamanna, Jason J.; Schapiro, Rebecca; Grin, Natalia; Hurtig, Carl V.; Miller, Joseph H.; Riley, Jonathan; Urquia, Lindsey; Federici, Thais; Boulis, Nicholas
Abstract : INTRODUCTION: Cell therapies represent a promising alternative treatment for neurodegenerative diseases of the spinal cord, and traumatic spinal cord injury. Cell survival, migration, proliferation and differentiation are intrinsic factors that greatly influence the therapeutic potential of cell therapies. Other factors like local inflammatory and immune response also play an important role. This study analyzed the migration patterns of fetal-derived neural precursors (NPCs) transplanted to the spinal cord of healthy Gottingen minipigs. METHODS: Fifteen female minipigs divided into 3 groups received 20 bilateral 10-, 25-, and 50-μL intraparenchymal injections of NPCs at a concentration of 10 000 cells/μL. After 21 days, animals were euthanized, perfused, and spinal cords were harvested for immunohistochemistry. Cell grafts (n = 5 per group) in both white matter (WM) and gray matter (GM) were quantitatively assessed in the 3-dimensional space using stereological volumetric calculations, and in the 2-dimensional space using Image J software to estimate migration distance from the epicenter in the rostrocaudal and transversal planes. RESULTS: Cell grafts exhibited different migration patterns in each anatomic compartment, regardless of injection volume. Cell grafts found in the WM migrated more in the rostrocaudal plane, whereas cell grafts found in the GM migrated similarly in the rostrocaudal and transversal planes. The 50-μL grafts in the WM were significantly wider ( P = .02) when compared with the 10-μL grafts, but not significantly wider when compared with the 25-μL grafts. Additionally, the total volume of GM occupied by the 25-μL grafts was significantly larger ( P = .02) when compared with the 10-μL grafts, but not significantly smaller when compared with the 50-μL grafts. These results suggest that 25 μL is the optimal injection volume at a cell concentration of 10 000 cells/μL. CONCLUSION: Understanding the migration patterns and other dynamics of different cell lines will allow neurosurgeons to ensure accurate delivery and maximize effectiveness of cell therapeutics in the spinal cord.